An Experimental Study on Solar Flat Plate Collector Using an Alternative Working Fluid - Manickavasagan, A.; Sampathrajan, A.; Manigandan, P. R.; Manivannan, S.; Eljeeva Emerald, F. Magdaline; Malarkodi, R.; Mangalam, S. (Universiti Putra Malaysia Press, 2005)
This paper describes the performance of a solar water heater with an alternative working fluid. A solar flat plate collector of fIxed orientation was fabricated and connected to a heat exchanger, which was kept inside the water storage drum. The developed collector was a low temperature device operating with the temperature range of ambient to 100°C. Acetone was selected as an alternative working fluid and allowed to re-eirculate in a closed loop. A shell and tube type heat exchanger (non-mixing) was designed and fabricated for the heat transfer between acetone and water. The solar intensity increased from 55 mw/cm2 at 8.30 am to 85 mw/cm2 at 1.30 pm and decreased to 64 mw/cm2 at 5.00 pm. The absorber plate temperature, which remained nearly constant for the first two hours, went up to 90°C in the next two hours. It was nearly constant from 11.00 am to 1.30 pm and then dropped down to 72°C in the afternoon. The hot fluid was found to loose heat to the surrounding water at more or less constant rate from 11.30 am to 5.00 pm. The highest temperature of acetone (70°C) was observed during 1.00 pm to 2.00 pm. The temperature of water increased from 30°C to a maximum of 62°C. Overall efficiency of the system was found to be 45% while considering the solar input to the heat gained by the water. Alternative working fluids such as acetone, methanol or ethanol may be considered for substituting water in the flat plate collector in view of the fact that the fluids have low boiling point coupled with high latent heat of evaporation.